2015
DOI: 10.4162/nrp.2015.9.3.227
|View full text |Cite
|
Sign up to set email alerts
|

Dual effects of a mixture of grape pomace (Campbell Early) and Omija fruit ethanol extracts on lipid metabolism and the antioxidant defense system in diet-induced obese mice

Abstract: BACKGROUND/OBJECTIVESWe investigated the effects of a combination of grape pomace (Vitis labrusca, Campbell Early) and Omija fruit (Schizandra chinensis, Baillon) ethanol extracts on lipid metabolism and antioxidant defense system in diet-induced obese mice.MATERIALS/METHODSForty male C57BL/6J mice were divided into four groups and fed high-fat diet (control group, CON) or high-fat diet added 0.5% grape pomace extract (GPE), 0.05% Omija fruit extract (OFE) or 0.5% GPE plus 0.05% OFE (GPE+OFE) for 12 weeks.RESU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 46 publications
1
4
0
Order By: Relevance
“…Interestingly, the grape seed cake diet produced a significant decrease in cholesterol concentration in the plasma of GS pigs, being in accordance with previous studies on laboratory animals and on humans, which demonstrated the protective antihyperlipidemic and antihyperglycemic effect of grape by‐products or (whole fruit) grape (Cho et al., ; Cui et al., ; Han et al., ). Polyphenols like catechin, gallic acid, epicatechin and other active compounds from grape seed reduced cholesterol absorption through the inhibition of pancreatic cholesterol esterase, which reduce the solubility of cholesterol in micelles and blood (Evans, Wilson, & Guthrie, ; Hui & Howles, ; Ngamukote, Makynen, Thilawech, & Adisakwattana, ).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Interestingly, the grape seed cake diet produced a significant decrease in cholesterol concentration in the plasma of GS pigs, being in accordance with previous studies on laboratory animals and on humans, which demonstrated the protective antihyperlipidemic and antihyperglycemic effect of grape by‐products or (whole fruit) grape (Cho et al., ; Cui et al., ; Han et al., ). Polyphenols like catechin, gallic acid, epicatechin and other active compounds from grape seed reduced cholesterol absorption through the inhibition of pancreatic cholesterol esterase, which reduce the solubility of cholesterol in micelles and blood (Evans, Wilson, & Guthrie, ; Hui & Howles, ; Ngamukote, Makynen, Thilawech, & Adisakwattana, ).…”
Section: Discussionsupporting
confidence: 88%
“…Previous studies with grape compounds revealed their significant anti‐inflammatory effect. A reduced expression of the inflammatory mediators after grape compounds action has been described in different cell types from different species (human, rat, mice) (Ahn, Lee, Kim, & Ha, ; Chuang et al., ; Han et al., ). For example, cocoa extracts or single flavonoids (epicatechin, catechin) decreased the production of inflammatory cytokines TNF‐ α , MCP‐1, IL‐6 and IL‐8 in stimulated macrophages and whole blood cells (Perez‐Cano, Massot‐Cladera, Franch, Castellote, & Castell, ); resveratrol, an active polyphenol present in grapes, exerted a chemoprotective effect on rat liver carcinogenesis by decreasing the pro‐inflammatory cytokines (Mbimba et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Omija ( Schizandra chinensis Baillon) fruit is traditionally used in asthma, nonproductive cough, sleep orgasm, nocturnal diaphoresis and chronic diarrhea. It also inhibits oxidative stress, inflammation, diabetes, carcinogenesis and protects against hepatic toxicity (Guo et al, 2008; Han et al, 2015; Jo et al, 2011; Szopa, Ekiert, & Ekiert, 2017). The combination of grape pomace and omija fruit ethanol extract (GO) given to db/db obese mice with type 2 diabetes on an HFD reduced hyperglycemia, adiposity, hepatic steatosis, inflammation, and oxidative stress (Cho et al, 2013; Cho et al, 2014; Cho et al, 2015a; Cho et al, 2015b).…”
Section: Medicinal Plants and Plant‐based Natural Products As A Thera...mentioning
confidence: 99%
“…The fruits have been utilized for thousands years as a superior drug for therapy of persistent dyspnoea and cough, frequent urination, severe sweating, shortness of breath, hepatitis, diabetes, and wasting-thirsting disease [2]. In addition, the extracts or metabolites from the plant were reported to have various biological efficacies such as anti-tussive, astringent, tonics [3], antioxidant [4], anti-inflammatory [5], anti-aging [6], anti-tumor [7], and inhibition of platelet aggregation [8] effects. The fruit of S. chinensis contains lignans, organic acids, monoterpenes, sesquiterpenes, and triterpenoids as major constituents [9].…”
Section: Introductionmentioning
confidence: 99%